A TiSe2‐Graphite Dual Ion Battery: Fast Na‐Ion Insertion and Excellent Stability. Issue 34 (1st July 2021) - Zheng, Runtian; Yu, Haoxiang; Zhang, Xikun; Ding, Yang; Xia, Maoting; Cao, Kangzhe; Shu, Jie; Vlad, Alexandru; Su, Bao‐Lian
Abstract: The sodium dual ion battery (Na‐DIB) technology is proposed as highly promising alternative over lithium‐ion batteries for the stationary electrochemical energy‐storage devices. However, the sluggish reaction kinetics of anode materials seriously impedes their practical implementation. Herein, a Na‐DIB based on TiSe2 ‐graphite is reported. The high diffusion coefficient of Na‐ions (3.21×10 −11 –1.20×10 −9 cm 2 s −1 ) and the very low Na‐ion diffusion barrier (0.50 eV) lead to very fast electrode kinetics, alike in conventional surface capacitive storage systems. In‐situ investigations reveal that the fast Na‐ion diffusion involves four insertion stage compositions. A prototype cell shows a reversible capacity of 81.8 mAh g −1 at current density of 100 mA g −1, excellent stability with 83.52 % capacity retention over 200 cycles and excellent rate performance, suggesting its potential for next‐generation large scale high‐performance stationary energy storage systems. Abstract : A TiSe2 ‐graphite Na‐DIB with fast kinetics and excellent cycling stability is for the first time proposed by combining a TiSe2 Na‐ion anode with an anion‐storing graphite cathode. Compared with other Na‐DIBs, the TiSe2 ‐graphite Na‐DIB significantly improves the Na‐ion insertion kinetics with superior cycle stability. The Na‐ion and PF6 − storage mechanism is investigated.